Myxomycetes (Physarum) Physarum stellatum - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (CABI, 2017)
Diagnostic features. Aside from the unusual star-shaped dehiscence of the sporocarp, the presence of a pseudocolumella distinguishes P. stellatum from other similar species with a dense but reticulate capillitium (P. globiferum (Bull.) Pers., P. murinum Lister, P. perfectum M. Peck and P. scoticum Ing).
Keywords: myxomycetes; міксоміцети; Physarum stellatum